Preparation method and application of MXene and lignin composite conductive paper-based sensor

By mixing the lignin nano -balls with MXENE, a composite electrical paper base sensor is formed, and the sensor performance of the MXENE material structure is weakened, and the high -value utilization of lignin is used to achieve a more stable sensor performance. And superior electrochemical performance.

CN119332535APending Publication Date: 2025-01-21TIANJIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411323331.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In application, MXene materials are prone to weaken their sensing properties due to structural oxidation. As a difficult-to-use biomass, lignin has a gap in the high-value utilization of biomass materials, making it difficult to effectively combine with MXene materials.

Method used

By preparation of wooden nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -nano -germ sensor, MXENE@通过 Composite electrical paper base sensor is formed, and lubu nano -balls are used as lubricants and intervals to expand the spacing of the MXENE sheet layer to prevent strain interruption.

Benefits of technology

Maintaining stable sensing performance in the case of 0 % to 90 % of the response, with a response time of 314ms and the recovery time of 569ms, which significantly improves the performance of the MXENE paper -based sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332535A_ABST
    Figure CN119332535A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an MXene and lignin nanosphere composite conductive paper-based sensor, the performance of the MXene-based sensor is improved by doping size-controllable lignin nanospheres prepared by an anti-solvent method into single-layer MXene, and the influence of complex reaction conditions such as chemical grafting on the performance of an MXene material is avoided. By doping the lignin nanospheres, the original uncontrollable microcrack mechanism is changed into an interlayer contact conductive mechanism, and application of MXene in more sensing fields is facilitated. According to the application of the MXene coated LNPs as a paper-based coating, multiple methods such as a single-layer coating, a double-side single-layer method and a single-side double-layer method are tried to endow the paper with the sensing performance, and a new method scheme is provided for functional application of the paper-based material in the sensing field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of two-dimensional materials, and in particular to a preparation method and application of a MXene@lignin composite conductive paper-based sensor. Background Art

[0002] Wearable sensors have made great progress in recent years with the development of materials science. Among them, a new type of strain sensor with MXene as the main sensing material has gradually been recognized and used by many researchers. However, the irreversible and difficult to control structural oxidation process makes it difficult to expand the application environment of MXene materials, which seriously hinders the widespread application of MXene. At the same time, in the high-value utilization of biomass materials, lignin, as a complex and difficult-to-use biomass, is more likely to be regarded as a "waste" in the field of biomass utilization, compared with cellulose, hemicellulose, etc.

[0003] There is currently a gap in the technology of combining MXene and lignin. There are defects in the MXene material itself, that is, its layered structure is easily weakened due to hydrogen bonds and van der Waals adhesion, which is a huge obstacle to the further application and development of MXene. The addition of lignin can undoubtedly solve this problem well. At the same time, due to the addition of lignin, the extensive overlapping structure of sheets and balls brings a more complex conductive structure and conductive path to the sensor, and also makes MXene-based sensors have a longer service life and better electrochemical performance. In the use of lignin, the lignin micro-nanospheres prepared by the anti-solvent method can be used as lubricants and spacers between MXene layers, expanding the distance between MXene layers while preventing the loss of sensing performance caused by the breakage of MXene during strain. In the prior art, there is a piezoresistive pressure sensor prepared by imitating the microstructure of ginkgo leaves. A hybrid film design made of MXene as the main sensing material is used to construct a pressure sensor with an array micromorphology composed of an embossed ginkgo leaf shape as the core deformation part. It can show ultra-high sensitivity at 403.46kPa-1 and a short response time of 99.3ms, showing potential applications in human motion detection and human-computer interaction. However, this design abandons the original MXene microcrack sensing mechanism, expands the interval between MXene layers by adding lignin nanospheres, and drives the coating to contact the MXene sheets under the condition of longitudinal extrusion force due to the deformation of the paper base, changing the conductive path, thereby realizing sensing. Compared with the prior art, this study is a control of the micromorphology of the ginkgo leaf-shaped array on a smaller scale. The randomly distributed lignin nanospheres and MXene sheets overlap each other at the microscopic level, which can build a more complex conductive network on a thinner coating.

[0004] In the prior art, researchers have pioneered the use of lignin as a positive electrode friction nanomaterial assembled into a friction nanogenerator, showing a maximum VOC of 204.34V, ISC of 6.86μA, QSC of 70.27nC and an instantaneous output power density of 836.64mW / m 2 . It can be used for self-powered sensing or mechanical energy collection, and this water-soluble biofilm can be reused five times through regeneration. This utilization of lignin is exactly our original intention. As a by-product of chemical pulp cooking, lignin has long been used as a low-value treatment method for alkali recovery and heat production, while ignoring the fact that lignin, as a natural, reproducible compound produced together with cellulose, can be used in a high-value manner through many means. The present invention prepares lignin nanospheres through the anti-solvent method, which can achieve a certain degree of controllability of the microstructure and size of lignin through a simple method for further utilization.

[0005] In recent years, some researchers have achieved a larger contact area and higher sensitivity by constructing a network of micro-convex structures of MXene / silver nanoflowers. This method, as the idea of ​​this article, prepares a higher performance MXene / lignin nanosphere coating by utilizing the better size control and cheaper cost of lignin nanospheres. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a MXene@lignin composite conductive paper-based sensor.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The preparation method of MXene@lignin composite conductive paper-based sensor comprises the following steps:

[0009] S1: LiF and hydrochloric acid are mixed and stirred to obtain an etching solution; MAX powder is added to the etching solution for etching; the etched product is washed to neutrality, a solvent is added, ultrasonicated in an ice bath and an inert gas flow, and centrifuged to swell to obtain a MXene aqueous dispersion;

[0010] S2: Aqueous dispersion of lignin nanospheres obtained by antisolvent method;

[0011] S3: Preparation of MXene@LNPs coating;

[0012] S4: The MXene@LNPs coating is applied to the paper-based surface by coating the aqueous dispersion of MXene and lignin nanospheres to obtain a MXene@LNPs paper-based sensor.

[0013] Preferably, in S1, after etching, the MXene needs to be cleaned and centrifugally swollen to separate a single-layer flaky MXene, wherein the solvent used for cleaning is divided into two stages. At the beginning of the reaction, 2 mol / L hydrochloric acid is used for cleaning to wash away LiF. When the pH reaches 1-2, deionized water is used for cleaning until the pH is 7-8.

[0014] Preferably, in S1, the MAX powder comprises Ti3C2T x 、Ti2CT x 、Nb2CT x 、Mo2CT x 、Ti4N3Tx、Ta4C3T x 、Cr2TiC2T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x At least one of .

[0015] Preferably, in S1, the mass volume ratio of MAX powder, LiF and hydrochloric acid is 2g:3.2g:50ml; the concentration of hydrochloric acid is 9mol / L; the etching reaction temperature is 35°C and the etching time is 48h.

[0016] Preferably, in S1, the ultrasonic power is 200 W and the ultrasonic time is 15 min.

[0017] Preferably, in S1, the solvent for centrifugal swelling includes at least one of water, anhydrous ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and methanol;

[0018] The centrifugal speed was 3500 r / min and the centrifugal time was 15 min.

[0019] Preferably, in S2, the solvent used in the anti-solvent method is an 80% ethanol-water solution, and the anti-solvent is deionized water, wherein the mass volume ratio of lignin, 80% ethanol-water solution, and water is 100 mg: 50 ml: 250 ml, and stirring is maintained during the anti-solvent method at a speed of 600 r / min.

[0020] Preferably, in S2, the lignin used is alkali lignin, and the lignin needs to be graded before anti-solvent pelletization.

[0021] Preferably, in S4, the preparation method of the MXene@LNPs coating is: MXene and LNPs are mixed by a blending method, and the mass ratio of MXene to LNPs is 1:5.

[0022] Preferably, in S4, the coating is combined with the paper base by coating, and the paper base is made of hardwood chemical pulp with a beating degree of 25°SR, and the basis weight of the paper base is 80 g / m 2 The coating is fixed on the paper surface after being coated and dried. The coating amount is 6 mg / cm 3 The concentration of the coating used was 15 mg / ml calculated based on the concentration of MXene; the coating was used after being concentrated.

[0023] Compared with the prior art, the present invention has achieved the following technical effects:

[0024] By adjusting the size and dosage of lignin nanospheres, the present invention can obtain a strain sensor that maintains a relatively stable GF under 0% to 90% strain conditions, and has a response time of 314ms and a recovery time of 569ms; compared with the original pure MXene paper-based sensor, there is a significant improvement; the present invention not only uses simple and easy-to-obtain materials, but also has a simple preparation method and mild reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Infrared spectra of MXene, LNPs, and MXene@LNPs prepared in Example 1 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention;

[0026] Figure 2 ΔR / R0 diagram of the MXene@LNPs paper-based sensor prepared in Example 1 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention at different strain levels;

[0027] Figure 3 The response time and recovery time diagram of the MXene@LNPs paper-based sensor prepared in Example 1 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention;

[0028] Figure 4 The R / R0 diagram of the MXene@LNPs paper-based sensor prepared in Example 1 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention at different gradient strain degrees;

[0029] Figure 5 This is a SEM image of MXene prepared in Example 1 of the method for preparing a MXene@lignin composite conductive paper-based sensor of the present invention;

[0030] Figure 6 This is a SEM image of MXene@LNPs prepared in Example 1 of the method for preparing the MXene@lignin composite conductive paper-based sensor of the present invention;

[0031] Figure 7 ΔR / R0 diagram of different MXene@LNPs ratios prepared in Example 2 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention;

[0032] Figure 8 ΔR / R0 diagram of the single-side double-layer coated MXene@LNPs paper-based sensor prepared in Example 3 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention;

[0033] Fig. 9 ΔR / R0 diagram of the double-sided single-layer coated MXene@LNPs paper-based sensor prepared in Example 4 of the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention;

[0034] Fig.10 This is a microscopic mechanism diagram of a paper-based sensor according to the preparation method of the MXene@lignin composite conductive paper-based sensor of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] like Figure 1-10 As shown, the present invention discloses a method for preparing a MXene@lignin composite conductive paper-based sensor, comprising the following steps:

[0037] S1: Mix LiF and hydrochloric acid and stir to obtain an etching solution; add MAX powder to the etching solution for etching; wash the etched product to neutrality, add solvent, ultrasonicate in an ice bath and inert gas flow, the ultrasonic power is 200W, the ultrasonic time is 15min, centrifugal swelling, the solvent for centrifugal swelling includes at least one of water, anhydrous ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and methanol; the centrifugal speed is 3500r / min, and the centrifugal time is 15min; obtain MXene aqueous dispersion; wherein, after the centrifugation, the supernatant contains a single layer of MXene, and the solvent is continued to be added to the lower layer, and the centrifugal operation is repeated after sufficient shaking and dissolution until the color of the supernatant becomes clear; the concentration of the MXene aqueous dispersion obtained by this method is (3-5) g / L, and it needs to be further concentrated before use. The concentration is usually carried out by centrifugation, the centrifugal speed is (8000-100000) r / min, and the centrifugal time is (15-25) min;

[0038] After etching, the MXene needs to be cleaned and centrifugally swollen to separate the single-layer flake MXene. The solvent used for cleaning is divided into two stages. At the beginning of the reaction, 2 mol / L hydrochloric acid is used for cleaning to wash away the LiF. When the pH reaches 1-2, deionized water is used to wash until the pH is 7-8. MAX powder includes Ti3C2T x 、Ti2CT x 、Nb2CT x 、Mo2CT x 、Ti4N3Tx、Ta4C3T x 、Cr2TiC2T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x At least one of; in said S1, the mass volume ratio of MAX powder, LiF, and hydrochloric acid is 2g:3.2g:50ml; the concentration of hydrochloric acid is 9mol / L; the etching reaction temperature is 35°C and the time is 48h;

[0039] S2: Obtaining an aqueous dispersion of lignin nanospheres by an anti-solvent method; wherein the solvent used in the anti-solvent method is an 80% ethanol-water solution, the anti-solvent is deionized water, wherein the mass volume ratio of lignin, 80% ethanol-water solution, and water is 100mg:50ml:250ml, stirring is maintained during the anti-solvent method, and the stirring speed is 600r / min; and the lignin used is alkali lignin, and the lignin needs to be graded before anti-solvent balling; in the lignin grading method, the alkali lignin is required to be dissolved in 80% ethanol-water solution, so the purchased finished alkali lignin needs to be dissolved in 95% ethanol-water first, the insoluble part is filtered out, and then dissolved in 80% ethanol-water solution, the insoluble part is removed, and the obtained lignin can be dissolved in 80% ethanol-water solution; the filtered filtrate is dried and used to prepare lignin nanospheres, and the lignin obtained by grading is soluble in 80% ethanol-water solution;

[0040] S3: preparing MXene@LNPs coating; the preparation method of MXene@LNPs coating is: MXene and LNPs are mixed by a blending method, and the mass ratio of MXene to LNPs is 1:5;

[0041] S4: The MXene@LNPs coating is applied to the surface of the paper base by a coating method to obtain a MXene@LNPs paper-based sensor; wherein the coating is combined with the paper base by coating, and the paper base is a hardwood chemical pulp with a beating degree of 25゜SR, and the paper base weight is 80g / m 2 The coating is fixed on the paper surface after being coated and dried. The coating amount is 6 mg / cm 3 The concentration of the coating used was 15 mg / ml calculated based on the concentration of MXene; the coating was used after being concentrated.

[0042] The thickness of the conductive coating of the present invention is 20-40 μm. Too thick a coating will cause fracture during the strain process. The thickness of the coating is essentially positively correlated with the coating amount and the concentration of the coating.

[0043] Example 1

[0044] S1: Add 3.2g LiF and 40mL HCl (concentration 9mol / L) to a polytetrafluoroethylene container, stir for 0.5h to prepare an etching solution; add 2g Ti3AlC2 MAX powder to the etching solution and stir for 48h at 40℃ for etching; centrifuge the etched product at 3500rpm with 2mol / L dilute hydrochloric acid for 1min, repeat the washing 3-4 times, and purify until the pH is 1-2; then centrifuge and wash under the same conditions, repeat 5-6 times, and purify until the pH is 6-7; in an ice water bath, add water to the washing obtained in S3, and place it in a nitrogen flow for ultrasonic treatment for 15min, with an ultrasonic power of 200W. Centrifuge again at 3500rpm for 15min, and after the precipitate is fully swollen, centrifuge to obtain a single layer of MXene in the supernatant;

[0045] S2: The obtained MXene slurry with a concentration of 5 mg / ml is further concentrated by centrifugation and then blended with lignin nanospheres. The centrifugal speed is 10000r / min and the centrifugal time is 20min. The purchased commercial alkali lignin needs to be dissolved in 95% ethanol-water first, the insoluble part is filtered out and then dissolved in 80% ethanol-water solution, and the insoluble part is removed to obtain lignin that can be dissolved in 80% ethanol-water solution. The filtered filtrate is dried and used to prepare lignin nanospheres. 100mg of the obtained lignin is dissolved in 50ml of 80% ethanol-water solution, and it is fully stirred to dissolve. After it is fully dissolved, 250ml of deionized water is slowly added as an anti-solvent at a speed of 5ml / min. Stirring is maintained during the addition process at a stirring speed of 600r / min. The obtained lignin nanosphere aqueous dispersion is concentrated after vacuum rotary evaporation at a temperature of 40°C, and ethanol in the dispersion is removed at the same time.

[0046] S3: The two prepared dispersions were blended in a mass ratio of 1:5, stirred thoroughly and set aside, and the concentration of the obtained MXene@LNPs conductive coating was 15 g / L;

[0047] S4: The coating is fixed to the prepared paper-based surface by coating, and dried under natural air-drying conditions to obtain a MXene@LNPs paper-based sensor. The coating thickness is 20-40 μm, and the coating amount is 5 mg / cm 2 .

[0048] Example 2

[0049] This example shows the effect of lignin nanospheres of different sizes on the performance of MXene@LNPs paper-based sensors. The preparation of raw materials is the same as S1 to S4 in Example 1. The difference is that the volume of the anti-solvent (deionized water) used in the preparation of lignin nanospheres by the anti-solvent method is 150 ml, 250 ml, and 350 ml.

[0050] Then, the MXene dispersion was blended with the aqueous dispersion of lignin nanospheres obtained by different anti-solvent methods at a ratio of 1:5, and the coating was fixed to the prepared paper surface by coating. The MXene@LNPs paper-based sensor was obtained by drying under natural air drying conditions. The coating thickness was 20-40 μm and the coating amount was 5 mg / cm 2 .

[0051] Example 3

[0052] This example shows the effect of different contents of lignin nanospheres on the performance of MXene@LNPs paper-based sensors. The preparation of raw materials is the same as S1 to S4 in Example 1.

[0053] Then, the MXene dispersion and the aqueous dispersion of lignin nanospheres were blended in a ratio of 1:1, 1:5, 1:10, and 1:15, and the coating was fixed to the prepared paper-based surface by coating and dried under natural air-drying conditions to obtain the MXene@LNPs paper-based sensor. The coating thickness was 20-40 μm and the coating amount was 5 mg / cm 2 .

[0054] Example 4

[0055] This example is the effect of single-sided double-layer coating on the performance of MXene@LNPs paper-based sensor. The preparation of raw materials is the same as S1 to S4 in Example 1.

[0056] Then, the MXene dispersion and the aqueous dispersion of lignin nanospheres were blended in a ratio of 1:5, and the coating was fixed to the prepared paper-based surface by coating. The MXene@LNPs paper-based sensor was obtained by drying under natural air-drying conditions. The coating thickness was 20-40 μm and the coating amount was 5 mg / cm 2 After drying, the same coating operation was repeated to obtain a single-sided double-coated MXene@LNPs paper-based sensor with a coating thickness of 30-50 μm and a coating amount of 10 mg / cm 2 .

[0057] Example 5

[0058] This example shows the effect of double-sided single-layer coating on the performance of MXene@LNPs paper-based sensors. The preparation of raw materials is the same as S1 to S4 in Example 1.

[0059] Then, the MXene dispersion and the aqueous dispersion of lignin nanospheres were blended in a ratio of 1:5, and the coating was fixed to the prepared paper-based surface by coating. The MXene@LNPs paper-based sensor was obtained by drying under natural air-drying conditions. The coating thickness was 20-40 μm and the coating amount was 5 mg / cm 2 After drying, the same coating operation was repeated on the uncoated side of the paper substrate to obtain a double-sided single-coated MXene@LNPs paper-based sensor with a coating thickness of 20-40 μm (single side) and a coating amount of 5 mg / cm 2 (Single layer).

[0060] The above description only indicates the experimental direction of the main embodiments of the present invention, and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a MXene@lignin composite conductive paper-based sensor, characterized in that: The following steps are involved: S1: Mix LiF and hydrochloric acid and stir to obtain an etching solution; Add MAX powder to the etching solution for etching; wash the etched product to neutrality, add solvent, ultrasonicate in an ice bath and inert gas flow, and centrifuge to swell to obtain a MXene aqueous dispersion; S2: Aqueous dispersion of lignin nanospheres obtained by antisolvent method; S3: Preparation of MXene@LNPs coating; S4: The MXene@LNPs coating is applied to the paper-based surface by coating the aqueous dispersion of MXene and lignin nanospheres to obtain a MXene@LNPs paper-based sensor.

2. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S1, after etching, the MXene needs to be cleaned and centrifugally swollen to separate a single-layer flaky MXene. The solvent used for cleaning is divided into two stages. At the beginning of the reaction, 2 mol / L hydrochloric acid is used for cleaning to wash away the LiF. When the pH reaches 1-2, deionized water is used for cleaning until the pH is 7-8.

3. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: The S1, MAX powders include Ti3C2T x 、Ti2CT x 、Nb2CT x 、Mo2CT x 、Ti4N3Tx、Ta4C3T x 、Cr2TiC2T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x At least one of the following, wherein the mass volume ratio of MAX powder, LiF and hydrochloric acid is 2g:3.2g:50ml; the concentration of hydrochloric acid is 9mol / L; the etching reaction temperature is 35°C and the etching time is 48h.

4. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S1, the ultrasonic power is 200 W and the ultrasonic time is 15 min.

5. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S1, the solvent for centrifugal swelling includes at least one of water, anhydrous ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and methanol; The centrifugal speed was 3500 r / min and the centrifugal time was 15 min.

6. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S2, the solvent used in the anti-solvent method is an 80% ethanol-water solution, and the anti-solvent is deionized water, wherein the mass volume ratio of lignin, 80% ethanol-water solution, and water is 100 mg: 50 ml: 250 ml, and stirring is maintained during the anti-solvent method at a stirring speed of 600 r / min.

7. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S2, the lignin used is alkali lignin, and the lignin needs to be graded before anti-solvent pelletization.

8. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S4, the preparation method of the MXene@LNPs coating is: MXene and LNPs are mixed by a blending method, and the mass ratio of MXene to LNPs is 1:

5.

9. The method for preparing the MXene@lignin composite conductive paper-based sensor according to claim 1, characterized in that: In S4, the coating is combined with the paper base by coating, and the paper base is made of hardwood chemical pulp with a beating degree of 25°SR, and the basis weight of the paper base is 80 g / m 2 The coating is fixed on the paper surface after being coated and dried. The coating amount is 6 mg / cm 3 The concentration of the coating used was 15 mg / ml calculated based on the concentration of MXene; the coating was used after being concentrated.

10. Application of the preparation method of the MXene@lignin composite conductive paper-based sensor according to claim 1 in the field of strain sensing.

Citation Information

Patent Citations

  • Preparation method of two-dimensional MXene-based self-cleaning ultrafiltration membrane

    CN114768551A

  • Preparation method of flexible conductive hydrophobic breathable sensor, sensor and application

    CN115748294A

  • Preparation method of metal organic framework material MXene lignin as lithium ion battery negative electrode material

    CN116706025A

  • Preparation method of lignin micro-nanospheres with adjustable size

    CN116731350A

  • Composite paper-based flexible sensing material, preparation method thereof and strain sensor

    CN116770636A

Cited By

  • Phase change microcapsule-MXene-modified polyacrylate fabric coating as well as preparation method and application thereof

    CN122446543A